Greenwashing Practices in Business Organizations: A Scoping Review - Adhikari, Ujjwal (Janaprakash Journal of Multidisciplinary Research, 2025)
As environmental consciousness grows among consumers, many businesses have begun marketing their products and services with an emphasis on environmental responsibility and ecological conservation. Unfortunately, not all these claims are genuine. Some companies deliberately mislead customers by making false or exaggerated environmental claims about their offerings, such practices are known as greenwashing. Since this deceptive behaviour is particularly prevalent in the business sector, this study seeks to identify common greenwashing tactics used by organizations and examine how these practices affect organizational performance and sales outcomes. The research employs a systematic literature review methodology, drawing documents from the Web of Science (WoS) database. The PRISMA framework guided the selection process, ultimately yielding 57 relevant documents focused on greenwashing practices in business organizations. A Meta table was constructed to synthesize findings and identify areas for future research. A consistent pattern emerged across the reviewed literature shows that, while greenwashing may generate positive results initially, sustained deceptive practices combined with increasing consumer awareness eventually led to detrimental effects on organizational operations and profitability. Based on this comprehensive review, a synthesized conceptual framework has been developed to guide subsequent research on greenwashing.”